1982
DOI: 10.1111/j.1651-2227.1982.tb09393.x
|View full text |Cite
|
Sign up to set email alerts
|

CONGENITAL LACTIC ACIDOSIS, Α‐KETOGLUTARIC ACIDURIA AND VARIANT FORM OF MAPLE SYRUP URINE DISEASE DUE TO a SINGLE ENZYME DEFECT: DIHYDROLIPOYL DEHYDROGENASE DEFICIENCY

Abstract: A 6-month-old girl with vomiting, hypotonia and motor retardation was found to have elevated blood lactate, pyruvate, and branched chain amino acids associated with ketoglutaric aciduria. The combination of a congenital lactic acidosis with a variant form of maple syrup urine disease and ketoglutaric aciduria suggested a defect of a single component, common to pyruvate dehydrogenase, to branched chain ketoacid dehydrogenase, and to alpha-ketoglutarate dehydrogenase. Dihydrolipoyl dehydrogenase is the common co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…This suggests that the affinity of whatever the central factor is for the branched-chain keto acid dehydrogenase is greater than those for pyruvate and 2-oxoglutarate dehydrogenase. It is consistent with what has been encountered in E3 deficiency in which elevated levels of alanine are regularly encountered (4,15), in contrast to maple syrup urine disease where they are depressed, and levels of leucine, isoleucine, and valine were normal or only slightly elevated (5,7,12,15,18).…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that the affinity of whatever the central factor is for the branched-chain keto acid dehydrogenase is greater than those for pyruvate and 2-oxoglutarate dehydrogenase. It is consistent with what has been encountered in E3 deficiency in which elevated levels of alanine are regularly encountered (4,15), in contrast to maple syrup urine disease where they are depressed, and levels of leucine, isoleucine, and valine were normal or only slightly elevated (5,7,12,15,18).…”
Section: Discussionsupporting
confidence: 63%
“…The latter is an FAD-and NADH-dependent activity believed to mainly have a prooxidant role (3). These findings together suggest that, under physiological conditions, DLD primarily functions as a DLD, playing a central role in the maintenance of energy metabolism (9)(10)(11)(12). Conversely, the moonlighting proteolytic activity of DLD could arise under pathological conditions, including the presence of dimer-destabilizing mutations or the acidification of the mitochondrial matrix (7).…”
Section: Discussionmentioning
confidence: 99%
“…The oligomeric state of DLD can change from dimeric to monomeric or tetrameric depending on the pH in the mitochondrial matrix, and changes in the oligomeric state of the protein have been shown to correlate with a shift from DDL activity (only present in dimeric and tetrameric DLD) to diaphorase activity (present in both oligomeric and monomeric forms of the protein) (7,8). Thus, DLD represents a highly versatile oxidoreductase with multiple critical roles in energy metabolism and redox balance (2,7,(9)(10)(11)(12).Here, we found that DLD can also function as a moonlighting protease. Moonlighting enzymes are a growing category of molecules that can accomplish multiple functions through a variety of mechanisms including, among others, localization to different cellular compartments, binding of different cofactors, and changes in oligomerization state (13).…”
mentioning
confidence: 99%
“…A deficiency, therefore, in this enzyme results in blocking of oxidative decarboxylation not only of pyruvate and a-ketoglutarate but of branched-chain ctketoacids, and causes serious neurological disease [6,7,9,10,13]. Therapeutic measures for this disease have been unsuccessful, with the exception of a large dose of lipoic acid, to which one patient partially responded [6].…”
Section: Introductionmentioning
confidence: 92%